KETIDAKFASIHAN BERBICARA PARA PEMERAN DALAM SERIAL DRAMA SHERLOCK OLEH SIR ARTHUR CONAN DOYLE (SUATU ANALISIS PSIKOLINGUISTIK) - GUE, IKA PERTIWI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This study which entitled â€œKetidakfasihan Berbicara Para Pemeran dalam Serial Drama Sherlock oleh Sir Arthur Conan Doyle (Suatu Analisis Psikolinguistik)â€ is an attempt to identify the types of speech disfluencies of the characters in the serial drama Sherlock and to analyze the causes of those speech disfluencies. In classifying and analyzing the collected data, the writer uses Fox-Tree (1995) and MacGregorâ€™s (2008) theory about the types of speech disfluencies and Bortfeldâ€™s et al. (2001) theory of what cause the speech disfluencies. It is found that silent pauses are occurred the most because of the increase of cognitive process that results to a heavy planning and delays in utterances. Repairs are occurred the fewest due to the fact that repairs change information that will affect listenersâ€™ comprehension. Therefore, people will monitor what they say more carefully to avoid repairing their utterances. The speech disfluencies of the characters in the serial drama Sherlock is mainly affected by variables such as, cognitive load, communication medium, topic under discussion, addressee characteristic, speaker characteristic, as well as social and situational factors. It is because we encounter those variables in almost every time. Age and conversation partner are found to be the fewest to cause speech disfluencies in the serial drama Sherlock as there arenâ€™t many older people and new characters in the serial drama. This study will help students and the next researchers in expanding their knowledge about speech disfluencies and language production. Â  Keywords: speech disfluencies, serial drama Sherlock, psycholinguistic analysis